Factors Associated with Unmet Respite Care Needs in Families of Children with Autism Spectrum Disorder - (:unkn) unknown (My University, 2017)
Background. One in sixty-eight children have Autism Spectrum Disorder (ASD). To optimize outcomes to families through use of respite care, we examined the prevalence of unmet respite care needs and associated factors in families of children with ASD, compared to families of children with special healthcare needs (CSHCN) without ASD. Design. An exploratory secondary analysis of the 2009-2010 National Survey of Children with Special Healthcare Needs (NS-CSHCN) was conducted using a non-experimental, descriptive, correlational design. The NS-CSHCN is a national cross-sectional telephone survey of 40,242 US households. The final sample included parents of children age 2-18 years old with ASD (n=935) and parents of CSHCN without ASD (n=1,583) who reported a need for respite care. Logistic regression was used to examine relationships between context factors that were aligned with the Individual and Family Self-Management Theory and unmet respite care needs. Results. Parents of children with ASD who had unmet respite care needs were predominantly white, well-educated, affluent mothers of male children 12-17 years old with limited functional status. Differences in prevalence of unmet respite care needs were found between parents of children with ASD (14%; n=558) and parents of CSHCN without ASD (2%; n=717). In parents of children with ASD, Child Functional Status, Hours/Week Providing Care, and Family Financial Burden were significant predictors of unmet respite care needs. Conclusions. The prevalence of unmet respite care needs in parents of children with ASD was seven times higher than parents of CSHCN without ASD. Screening all parents of CSHCN for unmet respite care needs is important, recognizing that parents of children with ASD, functional limitations and high caregiving demands are at highest risk for unmet respite care needs. Increased funding for and reimbursement of respite care services is needed to optimize family outcomes.
Keywords: Autism Spectrum Disorder; Children; Families; Respite Care; Special Needs; Unmet Needs